Pemberdayaan Kelompok Seni di Dusun Nitiprayan Bantul - Rini Raharti; Titi Laras; Bambang Jatmiko; Aditya Kurniawan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Service activities aim to help empower art groups through innovation and artistic creation. The target audience for the program is unproductive people, namely the Niti Budaya arts group in Nitiprayan hamlet, Ngestiharjo Village, Kasihan District, and Bantul Regency, which has 40 members. The problem experienced by partners is the lack of innovation and creativity in art groups, especially in dance, and the partners of these art groups are not yet well known to the wider community. Methodology: The partner's solution to the problem is to help the art studio conduct classical dance training in Sari Tunggal and Lambangsari and assist with digital marketing training. Apart from being attended by art groups, the training activities were also attended by local people who had an interest in the arts. Results: The results of the training program showed that the Niti Budaya arts group understood and mastered the classical dances, Sari Tunggal and Lambangsari, which were organized by the service team. The arts group's understanding of digital marketing has been demonstrated by promotional activities via social media and directly in the target market. With these activities, the arts groups increased in terms of understanding and well-being. Contribution: This activity will continue to be conducted to correct deficiencies and evaluate all activities. Limitations: This activity is beneficial for the community, especially the dance group in Nitiprayan.